2017
DOI: 10.1515/bpasts-2017-0059
|View full text |Cite
|
Sign up to set email alerts
|

Influence of raceway waviness on the level of vibration in rolling-element bearings

Abstract: Abstract. This paper provides a quantitative analysis of how raceway waviness (RONt) in 6304-type bearings affects their vibration. The waviness of bearing races was measured at the actual points of contact between the balls and the races. The measurements were conducted in the range of 16-50 undulations per revolution (UPR). The bearing vibration was analyzed in three bandwidths of frequency: low (LB) (50 ÷ 300 Hz), medium MB (300 ÷ 1800 Hz) and high HB (1800 ÷ 10 000 Hz), as well as in the full RMS bandwidth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 27 publications
0
26
0
1
Order By: Relevance
“…However, based on the results of vibration analysis, it can be concluded that the dominant vibration values were obtained in medium frequency band from 300 to 1800Hz. This may indicate excessive values of raceways waviness deviation (Adamczak, 2017a). Analyzing the results presented in Figure 3 it can be concluded that the increase the values of radial clearance causes an increase in the values of vibration level analysed in medium and high frequency band (see Fig.…”
Section: Research Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…However, based on the results of vibration analysis, it can be concluded that the dominant vibration values were obtained in medium frequency band from 300 to 1800Hz. This may indicate excessive values of raceways waviness deviation (Adamczak, 2017a). Analyzing the results presented in Figure 3 it can be concluded that the increase the values of radial clearance causes an increase in the values of vibration level analysed in medium and high frequency band (see Fig.…”
Section: Research Resultsmentioning
confidence: 86%
“…The natural frequencies of investigated bearings were as follows: frequency from rotation: 30 Hz, frequency from outer ring: 77.,22 Hz, frequency from inner ring: 132.78 Hz, frequency from balls: 105.45 Hz. The first step of research procedure was measurement of vibration velocity using measuring device known as Anderometer (Adamczak, 2017a). The examined bearings were mounted on spindle.…”
Section: Experimental Studymentioning
confidence: 99%
“…The RMS tested in these bands is typical for the control of newly manufactured rolling bearings. These bands are of course closely related with the rotational speed applied [12][13][14]. Each of the three bands has different supposed defects.…”
Section: Comparison Of the Vibration Signal Effective Valuementioning
confidence: 99%
“…Among them, the waviness error will affect the use of mechanical parts, so the impact of surface waviness has caused many scholars to study this in depth. Adamczak et al [3] found that an increase in the surface waviness on the inner and outer raceways causes an increase in the vibration level. This effect is most visible for the medium vibration frequency range.…”
Section: Introductionmentioning
confidence: 99%